Involvement in agro-tourism activities among fishermen community in two selected Desa Wawasan Nelayan villages in Malaysia - Muhammad, Mahazan; Hamzah, Azimi; Mohamed Shaffril, Hayrol Azril; Alby, Jeffrey Lawrence D'Silva; Md. Yassin, Sulaiman; Abu Samah, Bahaman; Tiraieyari, Neda (Canadian Center of Science and Education, 2012)
The agro-tourism activity in Desa Wawasan Nelayan is a new product of agro-tourism in Malaysia organized by Fisheries Development Authority of Malaysia. Local community involvement is important to the success of this agro-tourism programme. The main objective of this paper is to investigate the level of involvement of Desa Wawasan Nelayan community in agro-tourism activities. The data of this study is obtained from a survey of two Desa Wawasan Nelayan villages. A total of 220respondents were randomly selected to answer the questionnaire and the data was analyzed using the SPSS software.Based on this study, the overall mean score for level of involvement in agro-tourism activities in both states were moderate. However, both villages were found to have the highest mean score on involvement in environmental conservation activities and about their concern on the cleanliness of their village.The study recommends that more efforts should be taken by Desa Wawasan Nelayan community to be involved in agro-tourism activities that will significantly impact the local economy, social, and environment, and as a result will empower and support the cohesion of the community.